INNV-21. FEASIBILITY OF A VIRTUAL REALITY (VR) INTERVENTION TARGETING DISTRESS AND ANXIETY IN PRIMARY BRAIN TUMOR (PBT) PATIENTS AT THE TIME OF NEUROIMAGING: INTERIM ANALYSIS OF A PHASE 2 CLINICAL TRIAL. (14th November 2022) - King, Amanda; Roche, Kayla; Leeper, Heather; Vera, Elizabeth; Mendoza, Tito; Mentges, Kelly; Acquaye, Alvina; Adegbesan, Kendra; Boris, Lisa; Burton, Eric; Chambers, Claudia; Choi, Anna; et al.
Abstract: BACKGROUND: PBT patients experience high levels of distress and anxiety symptoms at the time of neuroimaging, yet few non-pharmacological interventions are available. This phase 2 clinical trial interim analysis explored feasibility of a VR relaxation intervention for a PBT population. METHODS: PBT patients seen at NIH were recruited to participate in this single arm trial conducted via telehealth. English-speaking, adult patients with upcoming neuroimaging who can self-report symptoms and have reported distress on previous MD Anderson Symptom Inventory-Brain Tumor assessments were eligible. Exclusion criteria include recent surgery or seizures, anxiety disorders, nausea, or visual deficits. The primary intervention consisted of a brief VR session done within 2 weeks prior to neuroimaging with patient-reported outcomes (PROs) collected before and immediately post-intervention, as well as 1 week and 4 weeks later, with self-directed VR use over 1 month. A qualitative phone interview was also completed to assess patient satisfaction. RESULTS: Fifty-five patients were screened and approached with 40 (73%) responding to initial reach-out and 20 ultimately enrolling (9 declines, 11 screen fails). Decline reasons included: no distress/anxiety (30%), treatment-related toxicities (11%), and unknown (59%). Seven (64%) failed screening due to exclusionary anxiety disorders (36% GAD, 18% PTSD, 9% claustrophobia). Of those enrolled, 65% were ≤ 50 years, 50% were male, 90% were White/non-Hispanic, 85% had good KPS ( > 80), 65% had high-grade tumors, and most were on active treatment. All enrolled patients completed the VR intervention and participation period, PROs questionnaires, weekly check-ins, and qualitative interview. Most patients (90%) reported frequent VR use with 7 mild adverse effects reported (headache, dizziness, nausea, neck pain). CONCLUSION: These findings suggest that this intervention is feasible for this population with high enrollment and study completion, though incidence of anxiety disorders was higher than anticipated and a comprehensive evaluation of this cohort is planned.